Analisis Likuiditas dan Profitabilitas terhadap Kebijakan Dividen pada Perusahaan Perbankan di Bursa Efek Indonesia Tahun 2019-2023 - Syahrani Arselia Putri; Diah Yudhawati; Rahmat Mulyana Dali (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
A company's dividend policy determines the company's profits will be distributed to investors as dividends or used as retained earnings. This research aims to analyze the influence of liquidity and profitability on dividend policy in banking companies on the Indonesia Stock Exchange in 2019-2023. The population in this research are banking companies listed on the Indonesia Stock Exchange in 2019-2023. The sample was selected using a purposive sampling technique and consisted of 9 banking companies. The data analysis method in this research is the panel data regression method. The results of this research show that partially or simultaneously liquidity and profitability have a significant effect on dividend policy.